Pengaruh Pengalaman, Etika Profesi, Objektivitas dan Time Deadline Pressure terhadap Kualitas Audit Di Badan Pengawas Keuangan dan Pembangunan Medan - Keumala Hayati; Ester Marianita Pangaribuan; Munawarah Munawarah; Wenny Anggresia Ginting (Universitas Muhammadiyah Sorong, 2019)
AbstrakThe objective of the research was to analyze and provide physical evidence: (1) The effect of Experience of auditor on the Audit Qaulity (2) Effect of Professional Auditor Ethics on the Quality of Audit, (3) Effect of Auditor Objectivity on the Quality of Audit, 4) Effect of Auditor Time Deadline Pressure on the Quality Audit, (5) Effect of Experience, Professional Ethics, Objectivity And Time Deadline Pressure simultaneously on the Quality Audit. The research populations were all auditors working at BPKP office, North Sumatra Province. The research samples used were chosen using saturated sampling technique, consisting of 95 respondents with return rate of 100%. The research data were analyzed using multiple regression analysis. Results of the analysis concluded that the (1) Experience and Professional Auditor Ethics significant positive effect on Audit Quality, (2) Objectivity and Time Deadline Pressure did not have any significant effect on Audit Quality, and (3) Experience, Ethics Profession, Objectivity, And Time Deadline Pressure simultaneously had a significant effect on Audit Quality. Keywords: Experience, Ethic Professional,Objectivity, Time Deadline Pressure, AuditQuality